A comparative study to evaluate the discrepancy in condylar guidance values between two commercially available arcon and non-arcon articulators: A clinical study - Mukesh Kumar Goyal; Shelly Goyal (Wolters Kluwer Medknow Publications, 2011)
Aim: The purpose of this study was comparative evaluation of sagittal condylar values of arcon and non-arcon articulators with cephalometric readings and to determine the amount of discrepancy in sagittal condylar guidance values between arcon and non-arcon articulators using same protrusive record. Materials and Methods: Twenty subjects in the age group of 19-35 years, free from temporomandibular joint dysfunction, and occlusal disharmony, with healthy dentition participated in the study. Hanau H2 (non-arcon type) and Hanau Wide-Vue (arcon type) articulators were programmed for sagittal condylar guidance values using the same protrusive record made in polysiloxane bite registration material with edge to edge degree of protrusion. The resultant values for both the articulators on either side were compared with values obtained from tracing of digital lateral cephalogram using Kodak Dental imaging Window software 6.6.3.0-C program. The tabulated data were subjected to statistical analysis, ANOVA (Fishers 'F' test) for group comparison, Tukey's HSD test for inter-comparison, student's unpaired 't' test for intra-group comparison, and level of significance (P) was calculated using the same. Results: The mean sagittal condylar guidance values of the three different groups were found to be very highly significant (P=0.001) and highly significant (P=0.002) on the right and left sides respectively. There was a very highly significant difference (P=0.001) and highly significant difference (P=0.003) between the arcon and non-arcon group on the right and left side respectively. No significant difference was found between the arcon and cephalometric group (P=0.284 right, P=0.853 left) and a statistically significant difference was found between the non-arcon and cephalometric group (P=0.049 right, P=0.015 left). On intragroup comparison there was no statistically significant difference in sagittal condylar values on the right and left sides. Conclusion: The mean difference in the sagittal condylar guidance values obtained from non-arcon and arcon articulators shows a low level of reproducibility, and no significant difference found in mean sagittal condylar values obtained from arcon articulator and cephalometric tracings indicates replication of sagittal condylar guidance value from image of articular eminence.